Technical efficiency of dairy farmers in Bihar, India: status and determinants - Dhiraj K Singh (Agricultural Economics Research Review, 2023)
Bihar’s share of the total milk produced in India rose from 3.2% in 2001–02 to 5.2% in 2018– 19, but the productivity of its dairy sector is lower than the national average. The low economies of scale, lack of institutional support, and dominance of small and marginal farmers have constrained the sector’s efficiency. The technical efficiency of dairy farmers—determined by a farmer’s herd size, the size of their holding of cultivated land, education, and experience— would be improved by skills development and technology transfer.